2020
DOI: 10.3390/rs12071125
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced 3D Point Cloud from a Light Field Image

Abstract: The importance of three-dimensional (3D) point cloud technologies in the field of agriculture environmental research has increased in recent years. Obtaining dense and accurate 3D reconstructions of plants and urban areas provide useful information for remote sensing. In this paper, we propose a novel strategy for the enhancement of 3D point clouds from a single 4D light field (LF) image. Using a light field camera in this way creates an easy way for obtaining 3D point clouds from one snapshot and enabling div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Second, the histogram stretching (HS) [ 27 , 28 ] was utilized to increase the contrast of all images. Take the i th image as an example, its minimum and maximum grayscale values and were calculated as: here ( w, h, c ) means the index of width, height, and channel directions along image , respectively.…”
Section: Dataset and Preprocessingmentioning
confidence: 99%
“…Second, the histogram stretching (HS) [ 27 , 28 ] was utilized to increase the contrast of all images. Take the i th image as an example, its minimum and maximum grayscale values and were calculated as: here ( w, h, c ) means the index of width, height, and channel directions along image , respectively.…”
Section: Dataset and Preprocessingmentioning
confidence: 99%
“…Earlier studies on similar 3D data visualization tasks have also observed superior benefits of kinetic depth over stereoscopic cues (e.g., Sollenberger and Milgram, 1993;Ware and Mitchell, 2005). It is possible that volumetric surface reconstruction from 3D point cloud data could provide more reliable geometric perceptive cues to infer 3D shape of objects depicted in single rendered images (e.g., Farhood et al, 2020). The results we obtained in our optic nerve reconstruction and visualization study suggest that the perceptual benefit of perspective cues provided by viewing slanted surfaces improves estimates of C/D ratio more than stereopsis alone.…”
Section: Discussionmentioning
confidence: 94%
“…An approach of Farhood et al [ 23 ] shows how the depth map, obtained by the light field camera, can be improved for getting the high-quality point cloud. The depth map is modified by histogram manipulations, aimed for better separation of depth layers, and then further enhanced by adding information about the objects’ edges.…”
Section: Related Workmentioning
confidence: 99%